Grid Stability and Power Quality Analysis of 65 MW Solar Photovoltaic Integration into the 132 kV Transmission Network in Port Harcourt, Nigeria: Grid Stability and Power Quality Analysis of 65 MW Solar Photovoltaic Integration into the 132 kV Transmission Network in Port Harcourt, Nigeria - Peace Barididum Biragbara (Institut Riset dan Publikasi Indonesia, 2025)
The global energy demand continues to rise steadily, prompting the need for clean, sufficient, and sustainable energy sources. This has led to a gradual shift from fossil fuels to renewable energy sources, although progress has been relatively slow. However, this research highlights the global shift towards renewable energy sources, driven by the need to reduce carbon emissions and foster sustainable energy practices. Problem, Nigeria faces frequent electricity shortages and grid instability, contributing to transmission and distribution losses of about 28%, despite the advancements, integrating substantial renewable energy sources into existing power grids presents challenges. To address these issues, wide-ranging analysis of solar irradiance data, grid stability, and power quality were conducted. The aim of this research is to analyse and simulate the strategy for integrating solar energy into Port Harcourt 132kV Mains Transmission Network. Grid stability analysis demonstrates robust performance, effective voltage regulation, and low harmonic distortion, ensuring minimal interference and efficient power supply. The method used in this research is called “Power flow simulation analysis method” This method involved evaluating solar energy potential using irradiance data, analysing grid stability through voltage and frequency regulation, risk management and environmental compliance were also examined to ensure project feasibility and sustainability. Results were obtained and specific findings reveal significant seasonal variations in solar irradiance, with optimal conditions during the dry season. Power quality remains stable, and essential for the reliable operation of sensitive equipment. The system operates at a high efficiency of 98% at a 100 MW load, underscoring the effectiveness of the integration strategy. The successful integration of a 65 MW solar energy system into the 132kV transmission line in Port Harcourt, aiming to enhance the region's renewable energy capacity and improve grid stability. It is therefore concluded that this study provides valuable insights and practical recommendations for optimising renewable energy integration, contributing to the advancement of sustainable energy solutions and grid modernisation.